Exhibition - Velvet Terrorism: Pussy Riot’s Russia - Alyokhina, Masha; Kjartansson, Ragnar; Sigurjónsdóttir, Ingibjörg; Pussy Riot's (MAC Montréal, 2023)
The performances, music, and videos created by the feminist punk art collective Pussy Riot, formed in Moscow in 2011, are characterized by provocative and politically charged lyrics and actions. Pussy Riot has shone a light on the brutal injustices that the Russian state inflicts on its citizens through political imprisonment, arbitrary arrests, extrajudicial executions, mysterious poisonings, aggressive surveillance, and other means of suppressing critical voices. The exhibition runs at the Montreal Museum of Contempory Art until March 10, 2024.
Keywords: 2023-10 October